Iowa RBA, August 21-22, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Iowa RBA update for August 21-22, 1995. Highlights of the update include sightings of Mississippi Kites, Piping Plover, Ruddy Turnstone, two Sanderlings and a Reeve (Ruff). Also included are handwritten notes for the next week's update with sightings of twenty-two Buff-breasted Sandpipers and three Ospreys. Epson - sheet feed/flatbed